Progress Report on Ph.D. Students’ Work on SmaRT Pack - Rekik, Emna; Tesfa, Asemu; Mekuria, Shigdaf; Getachew, Tesfaye; Mwacharo, Joram M.; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Two PhD studies are being supported during the reporting period. The two students are at different levels of their study. The studies are on 1) Analyzing Farmers' Perceptions of Climate Change in Ethiopia and Identifying the Genetic Factors Controlling Enteric Methane Emissions in Indigenous Sheep: A Comprehensive Field Study, and 2) Deciphering the impact of sheep community-based breeding programs on food security, women empowerment, GHG emission, and environmental adaptation under the extensive production systems in Ethiopia. Field data collection is progressing very well with both students, who have also drafted papers out of their data for publication. The details of their progress are in the report below.